Environmental politics and policy : - Steel, Brent (McGraw-Hill, 2003)
This text look at the subject on Environmental Politics and Policy from U.S. and international perspective expanding upon and reflecting the globalization of this important area of study. It focus on environmental issues included in the comparative examination are post-industrial countries, developing countries, post-Communist countries, and the U.S. In addition, chapters on science (what science is and how it fits into the political context), international law, and emerging issues (such as women and the environment) make this a strong and exciting text. (Publisher description)